The Unexplained Part of Public Debt - Dany Jaimovich; Ugo Panizza; Camil F.S. Campos (Inter-American Development Bank, Research Department, 2006)
This paper shows that budget deficits account for a relatively small fraction of debt growth and that stock-flow reconciliation, which is often considered a residual entity, is one of the key determinants of debt dynamics. After having explained the importance of the stock-flow reconciliation, the paper shows that this residual entity can be partly explained by contingent liabilities and balancesheet effects.
Keywords: 330; Öffentliche Schulden; Haushaltsdefizit; Welt